2015
DOI: 10.1039/c5ra15780c
|View full text |Cite|
|
Sign up to set email alerts
|

Removal of safranin-O dye from aqueous solution using modified red mud: kinetics and equilibrium studies

Abstract: Adsorption of safranin-O dye on SDS modified red mud at different pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…While Othman et al [ 65 ] suggested 1666.67 mg/g for the removal of MB dye, Tharaneedhar et al [ 60 ] reported 82.71 mg/g and Gourbanpour et al [ 18 ] obtained 810.4 mg/g for their developed composite. For SF dye removal, Abukhadra et al [ 66 ] and Sahu et al [ 67 ] reported 65.35 and 89.47 mg/g, respectively. The Q m values obtained in this work are 249.9 and 81.83 mg/g for MB and SF, respectively, both of which are within the range of reported values.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…While Othman et al [ 65 ] suggested 1666.67 mg/g for the removal of MB dye, Tharaneedhar et al [ 60 ] reported 82.71 mg/g and Gourbanpour et al [ 18 ] obtained 810.4 mg/g for their developed composite. For SF dye removal, Abukhadra et al [ 66 ] and Sahu et al [ 67 ] reported 65.35 and 89.47 mg/g, respectively. The Q m values obtained in this work are 249.9 and 81.83 mg/g for MB and SF, respectively, both of which are within the range of reported values.…”
Section: Modelingmentioning
confidence: 99%
“…While Othman et al [65] suggested 1666.67 mg/g for the removal of MB dye, Tharaneedhar et al [60] reported 82.71 mg/g and Gourbanpour et al [18] obtained 810.4 mg/g for their developed composite. For SF dye removal, Abukhadra et al [66] and Sahu et al [67]…”
Section: Isotherm Adsorptionmentioning
confidence: 99%
“…For Safranin, the absorbance peaks observed were mainly aliphatic primary amine N–H stretching (3,000–3,560 cm −1 ) and –OH stretching in the range of 3,589–4,000 nm in the control sample. However, in the decolorized test sample, the absorbance peaks varied: C–L stretching at 625 nm, C–N stretching 1,042–1,626 nm, C–C stretching 1,626 nm, C–H stretching 2,853–3,243 nm, and –OH stretching 3,283–3,564 nm ( Babu et al, 2015 ; Sahu and Patel, 2015 ). The shift in the peaks suggests a breakdown of functional groups that may have changed the original structure of the dyes in the decolorized test samples ( Chen et al, 2008 ; Ali et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample mixture was then analyzed using the instrument by mounting the sample on the sample holder using the ring holder and the transmittance scanned from the range of 4,000–400 cm −1 with a resolution of 1 cm −1 set for 20 scans per min ( Babu et al, 2013 ). The obtained peaks were compared with the published reference dye peaks ( Sigma-Aldrich, n.d. ; Sun et al, 2013 ; Maity et al, 2015 ; Sahu and Patel, 2015 ; Asses et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…As well as, this process is fast, easy, more efficient and regenerable. The role of SDS is the fixation of MB by a chemical bond and it leads to increase the amount REMOVAL OF METHYLENE BLUE FROM AQUEOUS SOLUTIONS WITH HYBRID BIOPROCESS 319 adsorbed in MB (Azizi et al, 2021;Que et al, 2018;Irani and Jadid, 2015;Sahu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%